Adverse Events, Functional Decline, and Access to Allied Health Therapies for Patients With Dementia During Acute Hospitalization. (August 2021) - Fox, Amanda; MacAndrew, Margaret; Wyles, Katy; Yelland, Catherine; Beattie, Elizabeth
The number of patients attending acute care hospitals with a diagnosis of dementia is increasing. The impact of hospitalization on function and adverse events is perceived to be greater for patients with dementia than those without. This study compared adverse events (falls, wounds, delirium, medication errors, infections, and incontinence), functional decline, and allied health therapy for patients with and without dementia ( n = 240). Patients with dementia experienced significantly more adverse events and constant observation by staff, were more dependent with mobility, hygiene and feeding, more often nil by mouth, confused, and incontinent. Patients with dementia were significantly more likely to receive speech and physiotherapy, although they did not significantly improve in function during their hospital stay. Conversely, patients without dementia significantly improved in mobility and continence. The unique health care needs of patients with dementia need to inform models of care, policy, and practice to support safe health care delivery in this vulnerable population.